2022
DOI: 10.3390/molecules27206901
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Herb-Drug Interactions of Glipizide with Andrographis paniculata (Burm. f.) and Andrographolide in Normal and Diabetic Rats by Validated HPLC Method

Abstract: Co-administered medicinal herbs can modify a drug’s pharmacokinetics (PK), effectiveness, and toxicity. Andrographis paniculata (Burm. f.) ethanolic extract (APE) and andrographolide (AND) (a potent CYP2C9 inducer/inhibitor) can alter the pharmacokinetic parameters of glipizide (GLZ). This study aimed to determine the potential pharmacokinetics of herb–drug interactions between GLZ and APE/AND in the plasma of normal and diabetic rats using the HPLC bioanalysis method. The glipizide bioanalytical method establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
4
0
1
Order By: Relevance
“…LC‐MS/MS study reported for immunoprotective potential against respiratory viral infections and the quality of A. paniculata capsules based on assay of three diterpenoids [18,29] . Pharmacokinetic herb‐drug interactions of glipizide with A. paniculata and andrographolide studied using a validated HPLC method in normal and diabetic rats [30] . A validated LC‐MS/MS method reported for clinical pharmacokinetics and presumptive phase‐II metabolic pathways following oral administration of herbal extract [31] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LC‐MS/MS study reported for immunoprotective potential against respiratory viral infections and the quality of A. paniculata capsules based on assay of three diterpenoids [18,29] . Pharmacokinetic herb‐drug interactions of glipizide with A. paniculata and andrographolide studied using a validated HPLC method in normal and diabetic rats [30] . A validated LC‐MS/MS method reported for clinical pharmacokinetics and presumptive phase‐II metabolic pathways following oral administration of herbal extract [31] .…”
Section: Resultsmentioning
confidence: 99%
“…[18,29] Pharmacokinetic herb-drug interactions of glipizide with A. paniculata and andrographolide studied using a validated HPLC method in normal and diabetic rats. [30] A validated LC-MS/MS method reported for clinical pharmacokinetics and presumptive phase-II metabolic pathways following oral administration of herbal extract. [31] In most of the cases the method reported is for single compound based or if it is multicompound based, it is of plasma originated or of product originated.…”
Section: Comparison Of the Proposed Methods With Other Reported Metho...mentioning
confidence: 99%
“…The pharmacokinetic behaviors of glipizide deduced using a substantiated RP-HPLC/UV bioanalytical method. Although APE increased the Cmax and AUC 0-t /AUC 0-∞ for Glipizide under both normal and diabetic rats, AND decreased its bioavailability in diabetic rats [34]. In a Drosophila model of polyglutamine (poly(Q)) disorders, Glipizide was shown to increase histone acetylation, upregulate insulin signaling, and decrease the genesis of neurodegenerative inclusion bodies.…”
Section: In-vivo Studies-mentioning
confidence: 97%
“…The pharmacokinetics of Divalproex Sodium significantly influenced by glipizide [24] Female Sprague-Dawley rats glipizide controlled glucose intolerance during pregnancy, renal oxidative stress, and kidney micro architectonic features equivalent to insulin [39] Albino mice Propranolol amplifies glipizide̓s hypoglycemic effect briefly in normal animals but consistently enhances it in diabetic ones, suggesting dosage adjustments when combined [25] Albino rats Atenolol boosted glipizide̓s hypoglycemic impact in diabetic rats [26] Male ICR mice Glipizide increased plasma insulin levels while decreasing kainic acid-induced neuronal cell death in the hippocampus and hyperglycemia [27] Albino rats Treating diabetes and hyperlipidemia jointly (glipizide + simvastatin) may have beneficial consequences [28] Male albino wistar rats Lycopene reduced blood glucose, cholesterol, and HDL alone and with Glipizide and Metformin [29] Rabbits Cimetidine enhanced Glipizide̓s hypoglycemic effects [30] Sprague Dawley rats glipizide does not prevent DENA-induced liver hepatocellular cancer [31] Male albino rats Glipizide is more effective against dyslipidemia, whereas metformin is better against glycemic control and oxidative stress [32] MMTV-PyMT mice ANP + Glipizide may treat breast cancer [33] TRAMP mice glipizide may be utilized to treat Prostate cancer [34] Male Wistar rats APE increased the Cmax and AUC 0-t /AUC 0-∞ of glipizide in both normal and diabetic rats, while andrographolide decreased its bioavailability [35] Drosophila Glipizide increased histone acetylation, insulin signaling, and neurodegenerative inclusion bodies [36] Rabbit Glipizide-aminophylline combinations are beneficial for diabetic patients [37] Male Wistar rats irbesartan and glipizide change blood pressure and pharmacokinetic parameters significantly [38] Sprague Dawley rats Lycopene + glipizide strong anti-diabetic effect (14th day) and reduce serum glucose, cholesterol, and increase HDL [40] Male albino rats The transfer of Glipizide from mucosal to serosal surface was enhanced by Lov and verapamil [41] Sprague Dawley Glipizide averted renal interstitial fibrosis, increased glomerular function, and reduced inflammatory infiltration [42] cLINIcAL TRIALS…”
Section: Mmtv-pymt Transgenic Animalsmentioning
confidence: 99%
“…Respon Kader Kampung Herbal Nginden Surabaya terhadap Sosialisasi Ramuan Jamu Saintifik untuk Diabetes Melitus Aspek kemudahan dalam pemahaman formula Ramuan jamu saintifik untuk penyakit DM memiliki nilai rata-rata 4,24 (84,8%) yang memiliki interpretasi sangat mudah dipahami. Aspek Kemudahan dalam pemahaman cara pengolahan Ramuan jamu saintifik untuk penyakit DM memiliki nilai 4,13 (82,6%) yang memiliki interpretasi sangat mudah dipahami.Jamu adalah obat tradisional yang terbuat dari bahan-bahan alami Warisan budaya tradisionalIndonesia karena kesehatan diturunkan dari generasi ke generasi(Sundhani et al, 2022). Bahan bahan ramuan pada jamu saintifik telah secara luas dimanfaatkan sehingga masyarakat awam lebih mudah dalam memahami(Dwi Kusumaningrum et al, 2022) (Sulasih et al, 2021).…”
unclassified